How Home Childbirth Takes Place with the Help of Untrained Family Members?: Qualitative Research - Kusumawati, Nila; Dhilon, Dhini Anggraini (GLOBAL HEALTH SCIENCE GROUP, 2024)
In Indonesia, childbirth is still taking place at home, with the help of either traditional birth attendants or untrained family members. This study aimed to explore how the childbirth process took place at home with the help of untrained family members. The study was qualitative research with a thematic analysis design. Eighteen respondents were recruited, as determined by data saturation. Semi-structured interviews using topic guides were performed to explore the phenomenon. Data was analyzed using Nvivo 11. The study emerged with six themes. They were unassisted home birth practice for labor progress methods, unassisted home birth practice for the baby delivery process, unassisted home birth practice for umbilical cord clamping procedure, unassisted home birth practice for umbilical cord cutting procedure, unassisted home birth practice for placenta delivery method, and unassisted home birth practice for the baby bathing process. Home childbirth with the help of untrained family members uses unique techniques and tools. There is a need for policymakers and relevant stakeholders to provide women and their family members with health education about safe facility childbirth.